2011
DOI: 10.1021/bi2008273
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Specificity of the Viral Suppressor of RNA Silencing Protein p19 toward Sequestering of Human MicroRNA-122

Abstract: Tombusviruses express a 19 kDa protein (p19) that, as a dimeric protein, suppresses the RNAs silencing pathway during infection by binding short-interfering RNA (siRNA) and preventing their association with the RNA-induced silencing complex (RISC). The p19 protein can bind to both endogenous and synthetic siRNAs with a high degree of size selectivity but with little sequence dependence. It also binds to other endogenous small RNAs such as microRNAs (miRNAs) but with lower affinity than to canonical siRNAs. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(50 citation statements)
references
References 50 publications
(129 reference statements)
3
47
0
Order By: Relevance
“…We have previously described the p19-Y73S mutation which completely abrogates siRNA binding. 21 We linked Y73S monomers into a linked dimer construct (2x-Y73S) in the same manner as the 2x-p19 construct and confirmed that the linked Y73S dimer remains incapable of binding siRNA ( Figure 2b ). When the TAT peptide is added to the C-terminus ( Figure 2c ), the fusion construct is able to bind siRNA with low affinity ( K d = 1.1 μmol/l) ( Figure 2e ).…”
Section: Resultsmentioning
confidence: 54%
See 3 more Smart Citations
“…We have previously described the p19-Y73S mutation which completely abrogates siRNA binding. 21 We linked Y73S monomers into a linked dimer construct (2x-Y73S) in the same manner as the 2x-p19 construct and confirmed that the linked Y73S dimer remains incapable of binding siRNA ( Figure 2b ). When the TAT peptide is added to the C-terminus ( Figure 2c ), the fusion construct is able to bind siRNA with low affinity ( K d = 1.1 μmol/l) ( Figure 2e ).…”
Section: Resultsmentioning
confidence: 54%
“…This dissociation constant is only slightly altered from that of wild-type p19 ( K d = 0.2 nmol/l). 18,21,27 We demonstrate that 2x-p19-TAT is able to deliver siRNA into Huh7 cells through the use of fluorescence microscopy and genetic reporter assays. Imaging the delivery of fluorescently labelled siRNA demonstrates that 2x-p19-TAT facilitates entry of siRNA into the cell ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…In an effort to specifically regulate RNA−protein interactions, Pezacki and colleagues engineered a virus protein p19 that is known to bind both siRNAs and miRNAs, albeit in different affinity ( Figure 10C). 133 A T111S mutant of p19 was generated and shown to improve the binding affinity toward miRNAs by 48-fold. The rationale for the improved binding was the bulging (bump) structure of miRNAs that fit better into the mutant p19 pocket ( Figure 10C).…”
Section: Acs Chemical Biologymentioning
confidence: 99%